Friday

April 18, 2014

April 18, 2014

Posted by **barry** on Monday, November 5, 2012 at 10:22am.

- math -
**Steve**, Monday, November 5, 2012 at 10:42am(3xy)^2 = 3^2 x^2 y^2 = 9 x^2 y^2

(2x^2z)^3 = 2^3 (x^2)^3 z^3 = 8 x^6 z^3

multiplying all that, we get

72 x^8 y^2 z^3

**Related Questions**

Algebra-Please check my answers - Posted by Jessie on Monday, October 18, 2010 ...

Algebra-Please check my answers - Posted by Jessie on Monday, October 18, 2010 ...

Math - Evaluate the expression for the given value. x = -2; y = 3; z = -1 -2x^2y...

Algebra-Please help - I'm really stuck on these problems- Simplify 6xy(3xy)^-2? ...

math help me pls - 1. Find the like terms in the expression y + 1.2y + 1.2z. (1 ...

math - Help?Simplify each expression.1. 3w – 10w a. 13w b. –7w c. –7 d. 7w 2. y...

Derive - Find the derivative of sin(2x + 3y)= 3xy + 5y-2. I have this so far 1) ...

Math 116 - simplify the expression -2(2z-7y)-z

math - Simplify: 2x^3y^2+ 4x^2z / 2x^4

Math - Simplify: 2x^3y^2=4x^2z / 2x^4